2016
DOI: 10.1002/1873-3468.12101
|View full text |Cite
|
Sign up to set email alerts
|

Congenital macrothrombocytopenia‐linked mutations in the actin‐binding domain of α‐actinin‐1 enhance F‐actin association

Abstract: Edited by Dietmar MansteinMutations in the actin cross-linking protein actinin-1 were recently linked to dominantly inherited congenital macrothrombocytopenia. Here, we report that several disease-associated mutations that are located within the actinin-1 actin-binding domain cause increased binding of actinin-1 to actin filaments and enhance filament bundling in vitro. These actinin-1 mutants are also more stably associated with the cytoskeleton in cultured cells, as assessed by biochemical fractionation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
3
25
2
Order By: Relevance
“…ACTN1 is a bundling protein that anchors actin to a variety of intracellular structures. Recently, Murphy et al () have reported that several disease‐associated variants located within the AB domain (p.(Arg46Gln), p.(Val105Ile), and p.(Glu225Lys)) cause increased binding of actinin‐1 to actin filaments. We hypothesize that ACTN1 variants induce more stable actin filaments, thereby impairing stretching and leading to shorter and thicker fibers in transfected CHO cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ACTN1 is a bundling protein that anchors actin to a variety of intracellular structures. Recently, Murphy et al () have reported that several disease‐associated variants located within the AB domain (p.(Arg46Gln), p.(Val105Ile), and p.(Glu225Lys)) cause increased binding of actinin‐1 to actin filaments. We hypothesize that ACTN1 variants induce more stable actin filaments, thereby impairing stretching and leading to shorter and thicker fibers in transfected CHO cells.…”
Section: Discussionmentioning
confidence: 99%
“…ACTN1 is an antiparallel, dimeric, actin cross‐linking protein composed of three domains: the N‐terminal actin‐binding (AB) domain composed of two calponin homology domains; the C‐terminal calmodulin (CaM) domain, which binds another actinin molecule, and the central rod domain composed of four spectrin‐like repeats (SRs) (Gimona & Mital, ; Murphy, Lindsay, McCaffrey, Djinović‐Carugo, & Young, ; Sjöblom, Salmazo, & Djinović‐Carugo, ). Twenty‐five ACTN1 variants have been described so far, of which 16 have been shown to alter the AB and CaM domains (Bottega et al, ; Faleschini et al, ; Guéguen et al, ; Kunishima et al, ) and induce varying degrees of actin network disorganization, while four variants were localized in the neck domains flanking the rod domain (Bottega et al, ; Kunishima et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the actin binding and the CH domains are responsible for interaction with actin, alterations of α‐actinin 1 are likely to impair the actin filament organization. It has been recently reported that some of these mutant forms exert a gain‐of‐function effect, resulting in an increased binding to actin, which is likely to affect its filament dynamics (Murphy et al , ). Indeed, the cytoskeleton structure is defective in cells expressing 15 out of the 26 variants identified in the ACTN1 gene, including the two novel mutations p.Trp128Cys and p.Pro233Leu of this paper (Fig ) (Kunishima et al , ; Bottega et al , ; Yasutomi et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated in blocking buffer (0.1% triton X-100, 5% goat serum and 2% bovine serum in PBS) prior to antibody incubation. All antibodies were diluted in 5% goat serum and 2% bovine serum in PBS (as described [ 20 ]). Cells were washed three times in PBS following each antibody incubation and coverslips were mounted onto glass slides using Fluoromount mounting media.…”
Section: Methodsmentioning
confidence: 99%